PEMANFAATAN KULIT BUAH NAGA MERAH (Hylocereus polyrhizus) SEBAGAI TEH HERBAL - Bambang Edi Purnomo; Faizah ' Hamzah; Vonny Setiaries Johan (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The purpose of this research was to obtain the best combination of drying time and drying temperature to produced herbal tea from dragon fruit peel which have high antioxidant. This research was carried experimentally using a Completely Randomized Design (CRD) two factorials;drying time (18, 21 and 24 hours); drying temperature(40°C, 50°C and 60°C) and three replication. Data obtained were statistically analyzed using Analysis of Variance (ANOVA) and continued with DNMRT test at 5% level. The result showed that drying time and drying temperature significantly influenced the moisture and ash contents, and significantly affected the IC50 value. The best treatment in this research was drying time 18 hours; 50°C with moisture content 14.03% (w/w), ash content 14.23% (w/w), IC50 Value 2.713 ppm, flavorful red dragon fruit peel, rather sepat taste, very red colour and the panelist likes overall herbal tea.   Keyword : red dragon fruit peel, herbal tea